Quality Management Transformation of Islamic Religious Higher Education: A Literature Review - Yudiawan, Agus; Himmah, Atikatul (Journal of Quality Assurance in Islamic Education (JQAIE), 2023)
This study aims to provide a brief and comprehensive understanding of the institutional governance of Islamic higher education based on quality management. A literature review explores various literature, books, articles, and regulations relevant to the study. Data is collected with a checklist of material classification and then analyzed by the content analysis method. Checking between libraries and rereading literature is done to tackle misinformation. This study explains that in reconstructing the management of superior Islamic higher education, management parties need to implement total quality management continuously and sustainably. All activities must be planned as well as possible so their implementation can produce satisfactory results. In addition, developing potential and resources needs to be done in a tiered and sustainable manner. That way, Islamic higher education will be able to respond to global challenges and continue to grow and develop.